2020
DOI: 10.1002/solr.202000460
|View full text |Cite
|
Sign up to set email alerts
|

Ternary All‐Small‐Molecule Solar Cells with Two Small‐Molecule Donors and Y6 Nonfullerene Acceptor with a Power Conversion Efficiency over Above 14% Processed from a Nonhalogenated Solvent

Abstract: An efficient organic solar cell (OSC) based on a ternary active layer consisting of two conjugated small‐molecule (SM) donors (FG3 and FG4) and a well‐known nonfullerene SM acceptor (Y6) is fabricated using a nonhalogenated solvent. An overall power conversion efficiency (PCE) of 14.31% is achieved, higher than that for the binary counterparts, i.e., 10.75% and 11.07% for FG3:Y6 and FG4:Y6, respectively. The short‐circuit current density (JSC) of the ternary active layer organ is related to the broader absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Guijarro et al reported efficient ternary SMPVs with conjugated small molecules FG3 and FG4 as donors and Y6 as the acceptor. 147 A PCE of 14.31% was yielded in the optimized ternary SMPVs, which is higher than that of FG3:Y6 based SMPVs (10.75%) and FG4:Y6 based SMPVs (11.07%). The J SC and FF values of the optimized ternary SMPVs are higher than the corresponding values of two binary SMPVs, and the V OC is in between that of two binary SMPVs.…”
Section: Ternary Smpvs Based On Two Donorsmentioning
confidence: 82%
“…Guijarro et al reported efficient ternary SMPVs with conjugated small molecules FG3 and FG4 as donors and Y6 as the acceptor. 147 A PCE of 14.31% was yielded in the optimized ternary SMPVs, which is higher than that of FG3:Y6 based SMPVs (10.75%) and FG4:Y6 based SMPVs (11.07%). The J SC and FF values of the optimized ternary SMPVs are higher than the corresponding values of two binary SMPVs, and the V OC is in between that of two binary SMPVs.…”
Section: Ternary Smpvs Based On Two Donorsmentioning
confidence: 82%
“…Without using BDT‐based small‐molecule donors, Guijarro reported a ternary ASM‐OSCs of FG3:FG4:Y6 [ 122 ] (Figure 9) where FG3 and FG4 are comprised of cyclopenta[2,1‐b:3,4‐b′]dithiophene (CPDT) derivatives and cyano rhodanine. Three component showed complementary absorption spectrum, and the energy transfer was found from FG3 to FG4.…”
Section: Ternary Strategymentioning
confidence: 99%
“…[11,[17][18][19][20][21] In comparison with PSCs, all-small-molecule organic solar cells (ASM-OSCs) composed of small-molecule donor (SMD) and small-molecule acceptor (SMA) have great potential for commercial application on account of the superiority of well-defined molecular structures, easy purification, and better repeatability. [22][23][24][25][26][27][28][29] To date, the PCE of ASM-OSCs has made great progress and transcended over 15% for binary OSCs. [30][31][32][33][34][35][36] Nevertheless, the value is still lagging far behind PSCs.…”
Section: Introductionmentioning
confidence: 99%